2009
DOI: 10.1002/hep.23506
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of functional hepatocytes from human embryonic stem cells under chemically defined conditions that recapitulate liver development

Abstract: Generation of hepatocytes from human embryonic stem cells (hESCs) could represent an advantageous source of cells for cell therapy approaches as an alternative to orthotopic liver transplantation. However, the generation of differentiated hepatocytes from hESCs remains a major challenge, especially using a method compatible with clinical applications. We report a novel approach to differentiate hESCs into functional hepatic cells using fully defined culture conditions, which recapitulate essential stages of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
427
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 462 publications
(449 citation statements)
references
References 41 publications
11
427
2
3
Order By: Relevance
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…First, ESCs could generate functional hepatocytes in vivo that are then engrafted efficiently within the host liver 6. A study reported that 2.5%–5% is necessary for reversing the liver injuries 59.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Celle-ci utilise des conditions chimiquement définies et suit les étapes clefs du développement hépatique [7] (Figures 1 et 2). Les trois étapes sont identiques à celles précédemment définies.…”
Section: Différenciation Hépatique Des Cellules Esunclassified
“…Nous avons montré que les conditions de différenciation des CSEh en hépatocytes que nous avons décrites permettent d'induire la différen-ciation d'iPS dérivées de fibroblastes humains en cellules de l'endoderme [29] puis en progéniteurs hépatiques [7]. Ainsi des études de fonctionnalité in vivo pourront être réalisées de façon comparative avec ces deux types de progéniteurs.…”
Section: Différenciation Des Ips En Hépatocytesunclassified